UPAYA MENINGKATKAN KEPERCAYAAN DIRI PESERTA DIDIK DENGAN TEKNIK SOSIODRAMA DI SMP - Ningsis, Lidya; Wicaksono, Luhur; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractEvery individual will requires confidence every day in various ways, including students in following the teaching and learning process in school. The good level of confidence is making good decision and easy to have a new friend, good relationships, and help individuals maintain the success. A common problem in this research is